2021
DOI: 10.51847/g6snno5aba
|View full text |Cite
|
Sign up to set email alerts
|

A review on updates in management and Treatment of Psoriasis

Abstract: Introduction: Introduction: Psoriasis is a rather common inflammatory skin disease that is characterized by the appearance of red scaly plaques and may affect any part of the body. There are certain factors that make psoriasis a challenge for physicians, these include: high prevalence, disability, chronicity, disfiguration, and associated comorbidities. The approach to the management of Psoriatic patients should also take into account the dermatological clinical features. This review would discuss and focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…As well the finding was supported by Zhang (34) Concerning psoriasis sites, the results of the present study illustrated that the most common psoriasis sites reported in both groups were knee and elbow followed by the hair scalp. These findings were in accordance with Alhammad et al (26) who stated that the most common sites were on the extensor surfaces of the limbs.…”
Section: Continuing Talking About Risk Factorssupporting
confidence: 92%
See 2 more Smart Citations
“…As well the finding was supported by Zhang (34) Concerning psoriasis sites, the results of the present study illustrated that the most common psoriasis sites reported in both groups were knee and elbow followed by the hair scalp. These findings were in accordance with Alhammad et al (26) who stated that the most common sites were on the extensor surfaces of the limbs.…”
Section: Continuing Talking About Risk Factorssupporting
confidence: 92%
“…These findings were in agreement with a recent study conducted at Banha city by Mohamed et al (33) about "Knowledge and Self-Care Practices among Psoriatic Patients in Benha City" and showed that the chief complaints of the studied patients were scaling of the skin, itching, erythema, and fatigue. In the same line with the above-mentioned findings Alhammad et al (26) confirmed that classical clinical manifestations are sharply demarcated raised lesions covered in silvery scales. As well the finding was supported by Zhang (34) Concerning psoriasis sites, the results of the present study illustrated that the most common psoriasis sites reported in both groups were knee and elbow followed by the hair scalp.…”
Section: Continuing Talking About Risk Factorssupporting
confidence: 75%
See 1 more Smart Citation
“…Almost 80% of the affected patients present with mild to moderate psoriasis [ 4 , 9 ]. Depending on disease severity, topical treatment, phototherapy, photochemotherapy, and systemic treatment may be used [ 8 , 9 , 10 ]. Apart from topical and systemic pharmacotherapy, adequate skincare is necessary to maintain remission of the skin lesions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even with localized lesions on the face or extremities, psoriasis had long been called "'the badge of shame". 1,2 Though many treatment options are available for localized psoriasis, each has its limitations and side effects. Therefore, the need for an effective topical agent that delivers the drug efficiently into the target site with minimal systemic side effects remains an aim in itself.…”
Section: Introductionmentioning
confidence: 99%